Portfolios, the Pied Piper of Teacher Certification Assessments: Legal and Psychometric Issues - Wilkerson, Judy R.; Lang, William Steve (Education Policy Analysis Archives, 2003)
Since about 90% of schools, colleges, and departments of education are currently using portfolios of one form or another as decision-making tools for standards-based decisions regarding certification or licensure (as well as NCATE accreditation), it is appropriate to explore the legal and psychometric aspects of this assessment device. The authors demonstrate that portfolios being used in a high-stakes context are technically testing devices and therefore need to meet psychometric standards of validity, reliability, fairness, and absence of bias. These standards, along with federal law, form the cornerstone for legal challenges to high-stakes decisions when students are denied a diploma or license based on the results of the assessment. The conclusion includes a list of requirements and caveats for using portfolios for graduation and certification decisions in a standards-based environment that help institutions reduce exposure to potential litigation.